2019
DOI: 10.1073/pnas.1810968117
|View full text |Cite
|
Sign up to set email alerts
|

OsmiR528 regulates rice-pollen intine formation by targeting an uclacyanin to influence flavonoid metabolism

Abstract: The intine, the inner layer of the pollen wall, is essential for the normal development and germination of pollen. However, the composition and developmental regulation of the intine in rice (Oryza sativa) remain largely unknown. Here, we identify a microRNA, OsmiR528, which regulates the formation of the pollen intine and thus male fertility in rice. Themir528knockout mutant aborted pollen development at the late binucleate pollen stage, significantly decreasing the seed-setting rate. We further demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…Prupe.4G202200, Fertilization Independent Endosperm (FIE) polycomb group protein, in Arabidopsis thaliana FIE regulates endosperm and embryo development and suppresses flowering during embryo and seedling development [ 64 ]. Prupe.4G207300 (uclacyanin) is associated with pollen grain development in rice [ 65 ]. Prupe.4G205500 (early nodulin-like protein 1) gene is reported to be engaged in determining the reproductive potential in Arabidopsis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prupe.4G202200, Fertilization Independent Endosperm (FIE) polycomb group protein, in Arabidopsis thaliana FIE regulates endosperm and embryo development and suppresses flowering during embryo and seedling development [ 64 ]. Prupe.4G207300 (uclacyanin) is associated with pollen grain development in rice [ 65 ]. Prupe.4G205500 (early nodulin-like protein 1) gene is reported to be engaged in determining the reproductive potential in Arabidopsis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the transport of flavonol‐3‐ O ‐sophorosides from the tapetum to the exine of pollen by disrupting the function of the flavonol sophoroside transporter (FST1) results in reduced pollen viability in A. thaliana (Grunewald et al, 2020). In rice, the development of intine, which is the inner layer of the pollen wall, also requires flavonoid metabolites, the production of which is regulated by OsUCL23, a member of the plant‐specific blue copper protein family of phytocyanins and the proton‐dependent oligopeptide transport (PTO) family of transporters (Zhang et al, 2020e).…”
Section: Biofunctions Of Phenylpropanoid Metabolitesmentioning
confidence: 99%
“…Some of these genes have already been characterized for their roles in anther development and/or internode elongation. Among these, DCW11 ( Fujii and Toriyama, 2008 ), OsSTRL2 [strictosidine synthase; ( Zou et al, 2017 )], EDT1 [ Earlier Degraded Tapetum 1 ; ( Bai et al, 2019 )], OsABCG3 [ATP-binding cassette transporter; ( Chang et al, 2018 )], OsGH3.8 ( Yadav et al, 2011 ), OsSPO11D ( Shingu et al, 2012 ), OsUAM3 ( Sumiyoshi et al, 2015 ), and OsUCL23 ( Zhang et al, 2020 ) have been shown to regulate diverse aspects of anther and pollen development. OsSTRL2 expression was detected only in tapetal cells and microspores, and knockout mutant resulted in male sterility mainly due to defects in anther wall and pollen exine formation ( Zou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%